Fibronectin 1B Gene Plays an Important Role in Loach Barbel Air-Breathing - Bing Sun (MDPI AG, 2021)
Loach (Misgurnus anguillicaudatus) is well known to perform air-breathing through the posterior intestine and skin. However, we find here for the first time a unique central vascular structure in the loach barbel, with a blood–gas diffusion distance as short as that of the posterior intestine. Under acute hypoxia, the distance of loach barbels became significantly shorter. Moreover, barbel removal significantly decreased air-breathing frequency of the loach. These findings imply that the barbel is another air-breathing organ of the loach. For further investigation of loach barbel air-breathing, a transcriptome analysis of barbels with air exposure treatment was performed. A total of 2546 differentially expressed genes (DEGs) between the T-XU (air exposure) and C-XU (control) group were identified, and 13 key DEGs related to barbel air-breathing were screened out. On this foundation, sequence, expression, and location analysis results indicated an important positive role of fibronectin 1b (fn1b) in loach barbel air-breathing. We further generated an fn1b-depletion loach (MT for short) using the CRISPR/Cas9 technique. It was indicated that depletion of fn1b could weaker barbel air-breathing ability. In conclusion, due to nonlethal and regenerative characteristics, the loach barbel, a newly discovered and fn1b-related fish air-breathing organ, can be a good model for fish air-breathing research.